Kompetencja językowa i komunikacyjna dzieci z zespołem Aspergera (ZA) - Bukowy, Agnieszka (Annales Universitatis Paedagogicae Cracoviensis Studia Paedagogica, 2021)
The article addresses the issue of language and communication competence of children with Asperger syndrome. It shows the specificity of the language behavior of this group, interpreted by many as the result of a high intelligence quotient, while the qualitative assessment of statements provides arguments indicating their ineffectiveness in the communication process. The presence of scientific and specialist terms in the formulated statements and more frequent selection of an adult as an interaction partner cause that these children are often misunderstood and excluded by peers